The Effect of Credit Risk on the Financial Stability of Rural Credit Banks in West Java: The Mediating Role of Profitability - Rahadian, Zaidan; Suherman, Ujang; Pranata, Rengga Madya (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the impact of credit risk on the financial stability of People's Credit Banks (BPR) in West Java from 2019 to 2023, considering the mediating role of profitability. Employing a quantitative methodology with descriptive and verificative approaches, the research utilizes secondary data from annual financial reports of BPRs obtained from the Financial Services Authority (OJK). The sample comprises 94 BPRs, with data analysis conducted using panel data regression and the Sobel test. Descriptive analysis reveals significant variations in credit risk levels, profitability, and financial stability across BPRs. Regression results indicate that credit risk exerts a negative but statistically insignificant effect on financial stability, while profitability demonstrates a positive and significant influence. Mediation analysis via the Sobel test confirms that profitability does not mediate the relationship between credit risk and financial stability. Simultaneously, both variables collectively contribute to financial stability, though external factors outside the model also play a role in shaping outcomes. The study concludes that enhanced credit risk management and improved profitability can bolster the financial stability of BPRs. Recommendations include strengthening credit risk governance, optimizing operational efficiency, and ensuring adequate capital buffers to maintain financial resilience amid economic challenges.